Primary band-shaped spheroidal degeneration of the cornea: three cases from two consanguineous families. Issue 5 (May 1986) - Hida, T; Kigasawa, K; Tanaka, E; Akiya, S; Tashiro, Y; Hosoda, Y
Abstract : Three cases of primary band-shaped spheroidal degeneration of the cornea from two consanguineous families are reported. In all cases vision deteriorated slowly, the deterioration beginning in childhood. Photophobia in childhood was also a common symptom, and two patients suffered from intermittent painful sensations. The occupational and environmental histories had no bearing on the cases. Histochemical study of the yellow, oily appearing deposits suggested that this material has a complex composition, with staining characteristics of both protein and acid-fast lipid.